Analisis Strategi Pemasaran Dalam Meningkatkan Volume Penjualan Pada UD. Tahu Murni Kota Gunungsitoli - Iman Telaumbanua, Tekun; Mendrofa, Yupiter; Beniah Ndraha, Ayler; Zalukhu, Yuterlin (Journal of Accounting and Finance Management, 2024)
Marketing has a crucial role in increasing product sales and introducing products to consumers. UD. Tahu Murni, located in Gunungsitoli City, is a business that focuses on tofu production with additional tempeh products. Although the business is still in operation, tofu production shows stagnation, with an increase only occurring on weekends. This is due to the lack of effective marketing strategies to attract a wider consumer base. This study aims to evaluate the marketing strategies implemented by UD. Tahu Murni in an effort to increase its sales volume. The main focus of this research is to identify the constraints faced in the marketing strategy as well as to propose improvement measures. Based on the results of the study, it was found that the marketing strategy of UD. Tahu Murni has not been optimized. The business still relies on traditional marketing methods such as word of mouth, direct sales, and direct distribution, which have proven to be slow and inefficient in expanding the market. Improving product quality and product planning based on consumer complaints is not enough to significantly increase sales volume.